Socioeconomic inequality as a predictor of unmet health needs in the older adult population of Serbia - Savić, Nikola; Radević, Svetlana; Jovanović, Verica; Ranković, Nevena; Lukić, Igor; Bogdanović Vasić, Slobodanka; Arandjelović, Branimirka; Bajić, Biljana; Mirković, Andrea; Arnaut, Aleksandra; Bajić, Borko; Vukosavljević, Svetlana; et al. (Frontiers in Public Health, 2024)
Objectives The aim of this paper is to assess the relationship between demographic and socioeconomic predictors and the unmet health needs of the older adult population in Serbia. Materials and methods The study is part of the Population Health Survey of Serbia, which was conducted in the period from October to December 2019 by the Institute for Public Health of Serbia “Dr. Milan Jovanović Batut” and the Ministry of Health of the Republic of Serbia. The research was conducted on a representative sample of Serbian residents in the form of a cross-sectional study. For the purposes of this research study, data on senior citizens, aged 65 and older, were used. Results Multivariate regression analysis of demographic characteristics that showed statistical significance in the univariate model as a whole explains between 4.2% (Cox & Snell R Square) and 5.9% (Nagelkerke R Square) of the variance of unmet health needs and correctly classifies 66.3% cases. Statistically significant demographic predictors were the region where the respondents live, level of education, and material condition. The results of the research show that the most dominant predictors of the unmet health needs of the older adult population are related to socioeconomic inequalities, financial reasons, and predictors related to the inaccessibility of health care. Conclusion The results suggest that individual socioeconomic predictors have a great influence on the emergence of unmet health needs of the older adult population in Serbia. Every third older adult resident did not receive the necessary health care, most often due to financial constraints.